ANALISIS PENGARUH HARGA DAN KREATIVITAS IKLAN TERHADAP KEPUTUSAN PEMBELIAN PADA MEDIA SOSIAL INSTAGRAM: Studi Kasus: Pada Toko Online Navqa - Nabilah Rachmadhanty, - (2019)
This research is a quantitative research that aims to determine the impacts of price and advertising creativity towards Navqa's online store. The population of this research reach 6750 people that were an Instagram user that also following Navqa online store. Size of the sample taken 85 respondents, with probability sampling especially multistage random sampling method. Data were collected by questionnaires. Analysis technic were used is PLS (Partial least Square) analysis method. The results of the research shows that (1), prices have a significant effect on buying decision with a path coefficient of 0.164 (2), advertising creativity has a significant effect on service quality with a path coefficient of 0.877.